Comparative Performance of Different Threshing Mechanisms on Pigeonpea Seed Quality - Lohan, Shiv K; Jakhar, S S; Kharb, R.P.S (Journal of Agricultural Engineering, 2007)
A study was conducted to compare hammermill, spike tooth and raspbar threshing cylinders at 3 combinations of cylinder speeds (400, 450, 500 rpm) and concave clearances (5, 10, 15 mm) for assessing quality of threshed pigeonpea seeds. Observations were recorded on the parameters namely, seed damage (%), threshing efficiency (%), standard germination (%) and electrical conductivity (m mhos?¹cm?¹seed?¹). Maximum seed damage (16.54%) was observed when threshing was done by hammermill cylinder with the cylinder speed of 500 rpm and concave clearance of 5 mm. The threshing efficiency decreased (99 to 91 %) with decreasing the cylinder speed from 500 to 400 rpm and increasing the concave clearance from 5 to 15 mm. The minimum seed damage (3.5%) and maximum germination (82%) were found under low cylinder speed (400 rpm) and high concave clearance (15 mm) in raspbar and spike tooth threshing cylinder. The germination was found significantly and negatively associated with seed damage, threshing efficiency and electrical conductivity. The electrical conductivity of seed leachates increased as the cylinder speed increased and concave clearance decreased.